Project Report on Integrated Voice Communication System - ROSHAN MATHEW, SHAMJA K MOIDEEN, ANOOB K P and ABU CYRIL JOSE (2003)
INTERNAL GUIDE: RATHNAKAR PATIL, MVJCE EXTERNAL GUIDE: D RAJAN, AIR TRAFFIC CONTROL, HAL
Keywords: Communication System